Removal of station nameboards, Esher for Sandown Park, Southern Railway, 1940 (1940)
1940 1939-1945 "Removal of station nameboards, Esher for Sandown Park, Southern Railway, 1940" [HFR0197], 1940 In May 1940, when the threat of invasion was strong, an Order was made to remove all road signs, street and station names in order to confuse the enemy. This photograph shows railway workers removing the sign at Esher and Sandown Park station.